TÜRKİYE’DE 2005-2017 TARİHLERİ ARASINDA HAYAT BİLGİSİ DERSİ İLE İLGİLİ YAPILMIŞ LİSANSÜSTÜ ÇALIŞMALAR ÜZERİNE BİR DEĞERLENDİRME. - POLAT, Hüseyin (Electronic Turkish Studies)
Elementary education classroom teaching program is an area of specialization including science expertise and doctoral program in Turkey. For that reason, the studies carried out and to be carried out on Life Sciences lesson in elementary education are remarkable for classroom teachers, pre-service teachers and academicians. The lesson of Life Sciences that has been lectured for totally 1980 hours in elementary education life of a student including four hours a week at the 1st and 2nd grade and three hours a week at the 3rd grade has a remarkable place for fulfilling general and specific purposes of the elementary education. In fact, there is no more such an assertive lesson in all school curriculums with the word of “life” it has on its name. The purpose of this research was to investigate postgraduate theses carried out on the lesson of Life Sciences between 2005 and 2017. In the research, qualitative research approach was adopted, and document analysis technique was used. In the research, as well, 95 postgraduate theses that were carried out in 2005 (f=4), 2006 (f=6), 2007 (f=9), 2008 (f=12), 2009 (f=7), 2010 (f=11), 2011 (=f11), 2012 (f=3), 2013 (f=8), 2014 (f=8), 2015 (f=8), 2016 (f=6) and 2017 (f=2) as being accessible in Council of Higher Education Thesis Center were regarded. According to the findings, it was determined that 95 postgraduate theses carried out on Life Sciences lesson for the last 12 years in Turkey were carried out most on “curriculum” , “teaching-learning process” and “course book”, and were carried out on “teaching-learning process” and “curriculum,” in doctoral theses, respectively.